Coordination within medical neighborhoods: Insights from the early experiences of Colorado patient-centered medical homes. Issue 2 (April 2016) - Alidina, Shehnaz; Rosenthal, Meredith; Schneider, Eric; Singer, Sara
Abstract : Background: The term "medical neighborhood" refers to relationships that patient-centered medical homes (PCMHs) seek to establish with other providers to facilitate coordinated patient care. Yet, how PCMHs can accomplish this coordination is not well understood. Purpose: Drawing upon organizational theory (Galbraith, 1974 ;Mintzberg, 1980 ;Thompson, 1967 ), we explored how PCMHs use coordination mechanisms to build and optimize their medical neighborhoods. Methodology: We used mixed methods, blending data collected via interviews and surveys with practice leaders and care coordinators at 30 months after a PCMH collaborative intervention in Colorado as well as surveys from all providers from 13 PCMHs before and 30 months after the intervention. We used thematic analysis to understand the role and use of coordination mechanisms by PCMHs and changes in the ability to coordinate and deliver care continuity. Findings: PCMHs drew on four coordination mechanisms to build relationships with their medical neighbors: interorganizational routines to improve reliability of information flow; information connectivity to facilitate continuity and safe care; boundary spanners to integrate care across silos; and communication, negotiation, and decision mechanisms to introduce shared accountability. When providers were fairly confident of the patient's diagnosis and management required sequential interactions (such as tests or procedures), PCMHs tended to coordinate care through interorganizational routines and information connectivity. When a diagnosis was less certain and required reciprocal interaction (i.e., consultation), PCMHs employed boundary spanners and communication, negotiation, and decision mechanisms. Practice Implications: Use of coordination mechanisms by PCMHs can help to improve care coordination in medical neighborhoods. All four mechanisms appear to be useful. The optimal mix of coordination mechanisms requires attention to patient context. Successfully building medical neighborhoods also requires meta-leaders, collaboration competencies, and high-quality relationships between providers in primary care, specialty care, and hospitals.